Prevalence of familial hypercholesterolemia and hyperlipoproteinemia(a) in patients with premature acute coronary syndrome - U. V. Chubykina; M. V. Ezhov; O. I. Afanas’eva; E. A. Klesareva; N. A. Tmoyan; S. N. Pokrovsky (Российский кардиологический журнал, 2022)
Aim. To evaluate the prevalence of familial hypercholesterolemia (FH) and hyperlipoproteinemia(a) (HLP(a)) in patients with premature acute coronary syndrome (ACS).Material and methods. The study included 120 patients with ACS up to 60 years (mean age, 53±7 years, 104 (87%) men) and 44 people from the comparison group without atherosclerotic cardiovascular diseases and dyslipidemia (mean age, 48±11 years, 19 (43%) men). All patients with ACS underwent coronary angiography. The lipid profile and lipoprotein(a) (Lp(a)) were determined in all patients.Results. The prevalence of HLP(a) in patients with premature manifestation of ACS was 41% (n=49), possible FH — 25% (n=30), combination of FH and HLP(a) — 13% (n=15). In the comparison group, an increased concentration of Lp(a) was detected in 14% (n=6). Based on the analysis of operating characteristic curves, Lp(a) ≥30 mg/dL had the maximum significance for ACS with a sensitivity of 40% and a specificity of 86% (area under the curve, 0,6; 95% confidence interval (CI), 0,5-0,7, p<0,05), and Lp(a) >15 mg/dl was associated with two or more coronary artery lesions with a sensitivity of 67% and a specificity of 65% (area under the curve, 0,7; 95% CI, 0,6-0,7, p<0,01). On logistic regression analysis, age (odds ratio (OR). 1,1; 95% CI, 1,0-1,2, p<0,05), smoking (OR, 7,5; 95% CI, 2,5-22,0, p<0,001) and Lp(a) ≥30 mg/dl (OR, 6,7; 95% CI, 1,1-39,7, p<0,05) are independently associated with premature ACS. Only Lp(a) ≥15 mg/dL was associated with multivessel coronary artery disease in these patients (OR, 3,8; 95% CI, 1,52-9,74, p<0,01).Conclusion. Every fourth patient with premature ACS has FH, while almost every second has HLP(a), and every eighth has a combination of FH and HLP(a). HLP(a) is associated with ACS up to 60 years of age and multivessel coronary artery disease in these patients.